The Sports Connection, integrated simulation. Microsoft Office 2003 - Susie H. VanHuss (Thomson/South-Western, 2006)
THE SPORTS CONNECTION reinforces essentials applications skills, such as word processing, desktop publishing, spreadsheet, database, and electronic presentation. This intermediate/advanced simulation is different from other typical document production simulations in that it provides students unique opportunities to go beyond the basics as they apply creativity in problem solving, decision making, flexibility, and more